The Swedish Perception of European Security in Light of the Crisis in Ukraine - Kobierecka, Anna (International Studies. Interdisciplinary Political and Cultural Journal, 2016)
The events in Ukraine, the annexation of Crimea, and the Russian attitude towards Ukraine show an evident change in European relations. The escalation of conflict between Russia and Ukraine however does not affect only those two countries, but also those in the nearest vicinity. Especially in Scandinavian and Nordic countries change in social ambience can be observed. The aim of this article is essentially to analyze Swedish reaction to the Ukrainian Crisis, the change in Swedish attitude towards international security systems, especially NATO, and Swedish perception of its national safety.